Tourist arrivals to Muslim countries: is religion important - Mat Ghani, Gairuzazmi (Cognizant, LLC., 2019)
Tourism is an important source of income for many countries, and religion is one of the factors shown to promote tourist arrivals. An important development in the tourism sector is the expansion of Islamic tourism products. If tourists from Muslim countries prefer to visit other Muslim countries, then the promotion of Islamic tourism products should focus on Muslim countries. This study uses the bilateral tourism flows gravity model to examine the Muslim country effect: that is, whether the number of tourist arrivals to Muslim countries is higher from Muslim countries than from non-Muslim countries. The analysis involved two steps. First, a least square dummy variables method was used using global level data. Second, the Muslim country effect was examined on the country level using tourist arrivals data for individual Muslim countries. The analysis shows that the Muslim country effect is positive at the global level but varies on the individual country level.